Atypical Enostoses—Series of Ten Cases and Literature Review - Thomas Bedard; Mujtaba Mohammed; Serenella Serinelli; Timothy A. Damron (Medicina, 2020)
Bone islands (BI; enostoses) may be solitary or occur in the setting of osteopoikilosis (multiple bone islands) and are sometimes associated with Gardner’s Syndrome (osteopoikilosis and colonic polyposis). Characteristic features of bone islands are (1) absence of pain or local tenderness, (2) typical radio dense central appearance with peripheral radiating spicules (rose thorn), (3) Mean CT (computerized tomography) attenuation values above 885 Hounsfield units (HU) (4) absence of uptake on bone scan and (5) radiographic stability over time. However, when enostoses display atypical features of pain, unusual radiographic appearance, aberrant HU, increased radiotracer uptake, and/or enlargement, they can be difficult to differentiate from more sinister bony lesions such as osteoblastic metastasis, low grade central osteosarcoma, osteoid osteoma and osteoblastoma. In this retrospective case series, the demographic, clinical, radiographic, treatment and outcome for ten patients with eleven atypical bone islands (ABI) are presented, some showing associated pain (5), some with atypical radiographic appearance (3), some with increased activity on BS (4), some with documented enlargement over time (7), one with abnormal CT attenuation value, some in the setting of osteopoikilosis (2), one in the setting of Gardner’s Syndrome and one osteoid osteoma simulating a bone island. This series represents the spectrum of presentations of ABI. Comprehensive review of the literature reveals that the previous largest series of ABI showing enlargement as the atypical feature was in younger patients with jaw BI. Hence, this represents one of the largest series reported of ABI of all types in adults.